2018
DOI: 10.1002/ncp.10091
|View full text |Cite
|
Sign up to set email alerts
|

High‐Protein Hypocaloric Nutrition for Non‐Obese Critically Ill Patients

Abstract: High-protein hypocaloric nutrition, tailored to each patient's muscle mass, protein-catabolic severity, and exogenous energy tolerance, is the most plausible nutrition therapy in protein-catabolic critical illness. Sufficient protein provision could mitigate the rapid muscle atrophy characteristic of this disease while providing urgently needed amino acids to the central protein compartment and sites of tissue injury. The protein dose may range from 1.5 to 2.5 g protein (1.8-3.0 g free amino acids)/kg dry body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 118 publications
0
32
1
1
Order By: Relevance
“…The concept of hypocaloric, high‐protein feeding as a nutrition strategy in the ICU has been garnering attention in recent years, in part owing to the work of Rugeles et al, who demonstrated that use of a 1.7 g/kg and 15 kcal/kg/d nutrition regime reduced severity of illness and hyperglycemia compared with a standard nutrition intervention with 25 kcal/kg/d and 20% protein calories . The European Society of Intensive Care Medicine's Early Enteral Nutrition Practice Guidelines recommend clinicians should not aim to cover full energy targets in early days of ICU admission and acknowledge hypocaloric feeding appears safe, whereas provision of excess energy may be harmful .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The concept of hypocaloric, high‐protein feeding as a nutrition strategy in the ICU has been garnering attention in recent years, in part owing to the work of Rugeles et al, who demonstrated that use of a 1.7 g/kg and 15 kcal/kg/d nutrition regime reduced severity of illness and hyperglycemia compared with a standard nutrition intervention with 25 kcal/kg/d and 20% protein calories . The European Society of Intensive Care Medicine's Early Enteral Nutrition Practice Guidelines recommend clinicians should not aim to cover full energy targets in early days of ICU admission and acknowledge hypocaloric feeding appears safe, whereas provision of excess energy may be harmful .…”
Section: Discussionmentioning
confidence: 99%
“…The average daily energy prescription was 1638.6 kcal ± 317.2 (990-2500) or 17.8 kcal/kg ± 5.4 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). The average energy intake across all days (including calories from fatbased medication) was 1523.9 kcal/d ± 403.6 (693.0-2557.5) or 17.3 kcal/kg/d (±5.2, 8.7-27.8).…”
Section: Energymentioning
confidence: 99%
See 3 more Smart Citations